Empirical observation : remuneration disclosure practices in Singapore - Koh, Boon Hui (2008)
This research aims to investigate factors affecting the quality of remuneration disclosure engaged by companies under the guidance of Singapore Code of Corporate Governance, Principle 9. Possible underlying reasons to the factors affecting the level of disclosure are examined and discussed in greater details in this study.